Evaluating the Impact of Patient No-Shows on Service Quality - Marbouh, Dounia; Khaleel, Iman; Al Shanqiti, Khawla; Al Tamimi, Maryam; Simsekler, Mecit Can Emre; Ellahham, Samer; Alibazoglu, Deniz; Alibazoglu, Haluk (Risk management and healthcare policy, 2020)
Patient no-shows are long-standing issues affecting resource utilization and posing risks to the quality of healthcare services. They also lead to loss of anticipated revenue, particularly in services where resources are expensive and in great demand. In order to address common reasons why patients miss appointments, this study reviews the current literature and investigates various tools and methods that have been implemented to mitigate such issues. Further, a case study is conducted to identify the rate of no-shows and underlying causes at a radiology department in one of the leading hospitals in the MENA region. Our results show that the no-shows are high due to multiple factors, such as patient behavior, patients' financial situation, environmental factors and scheduling policy. In conclusion, we generate a list of recommendations that can help in reducing the rate of patient no-shows, such as patient education, application of dynamic scheduling policies and effective appointment reminder systems to patients.